The invention and decline of Israeliness : state, society, and the military - Kimmerling, Baruch (S. Mark Taper Foundation imprint in Jewish studies., 2001)
This thought-provoking book, the first of its kind in the English language, reexamines the fifty-year-old nation of Israel in terms of its origins as a haven for a persecuted people and its evolution into a multi- cultural society. Arguing that the mono-cultural regime built during the 1950s is over, Baruch Kimmerling suggests that the Israeli state has divided into seven major cultures.